Use of highly sensitive C-reactive protein for followup of Wegener’s granulomatosis - Kälsch, Anna-Isabelle; Csernok, Elena; Münch, Dominik; Birck, Rainer; Yard, Benito A.; Gross, Wolfgang; Kälsch, Thorsten; Schmitt, Wilhelm (The journal of rheumatology, 2010)
Objective. Since Wegener’s granulomatosis (WG) represents a relapsing disease, efforts have been made to reliably predict relapses using blood tests. Followup measures such as conventionally determined C-reactive protein (CRP), antineutrophil cytoplasmic antibody (C-ANCA) titer, and proteinase-3 (PR3) ELISA are applied. We evaluated whether during remission elevated highly sensitive CRP (hsCRP) precedes relapse as a marker of subclinical inflammation and thus might improve clinical assessment. - Methods. We investigated 227 sera of 57 patients with WG: 74 sera collected from patients in remission who subsequently relapsed (before relapse), 30 sera collected during relapse, and 123 sera from patients in remission without relapse. We also distinguished between major and minor relapse. hsCRP, conventionally determined CRP (CRP), C-ANCA, PR3-ELISA, and erythrocyte sedimentation rate (ESR) were measured using commercial kits, and levels were correlated to clinical status. - Results. Only hsCRP and ANCA titer, but not CRP levels, were higher in sera from patients who subsequently relapsed versus those who did not, indicating patients at risk. Levels of hsCRP, CRP, and ESR were higher in sera collected during relapse than in the sera before relapse. hsCRP, conventional CRP, and ESR were also higher in samples collected during major relapse than before major relapse. Looking at the levels just before relapse compared to previous levels during remission, none of these measures rose directly before the clinical manifestation of the relapse. - Conclusion. Our study provides evidence for an additional value of hsCRP in the clinical assessment of patients with WG.
Gesehen am 10.10.2023